2005
DOI: 10.1678/rheology.33.1
|View full text |Cite
|
Sign up to set email alerts
|

Flow Property and Micellar Structures in Capillary Flows of Surfactant Solutions

Abstract: Flow property, which is expressed by the relation between wall shear stress and apparent shear rate, is examined in the flows of surfactant solutions through various capillaries. Furthermore, small angle light scattering (SALS) experiments are carried out in the flow through a slit cell. In the present experiments, aqueous solutions of Cetyltrimethylammonium bromide (CTAB) and Sodium Salicylate (NaSal) are used. The flow curve has a break point and its slope below the bending point significantly depends on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…32,33) These results suggest that the sudden protrusion relates to changes in micellar structure and rheological properties due to the flow.…”
Section: Growth Phenomenon Of Viscous Fingers In Polymer Solutions Anmentioning
confidence: 85%
“…32,33) These results suggest that the sudden protrusion relates to changes in micellar structure and rheological properties due to the flow.…”
Section: Growth Phenomenon Of Viscous Fingers In Polymer Solutions Anmentioning
confidence: 85%
“…[7][8][9][10][11][12] Kadoma et al [7][8][9] observed the change of SALS pattern at various shear rates (simple shear flow) with various excess salt ratios (Y) to investigate its effect on flow-induced orientation and concentration fluctuations for CTAB/NaSal solutions. They reported the relationship between several multiconnected networks of micelles and the SALS patterns.…”
Section: 6)mentioning
confidence: 99%
“…Moreover, they tried to estimate the relaxation time using the SALS pattern and obtained good agreement with the data from mechanical rheological measurement. Hashimoto et al 10) conducted an experiment to investigate the development of micellar structures by examining the flow of CTAB/NaSal in a capillary rheometer. They found that the flow curve has a bending point, and shear thinning happens at high shear rate after the bending point.…”
Section: 6)mentioning
confidence: 99%
“…4) Our research group also has studied the flow of CTAB/NaSal solutions, e.g. the relation between flow properties and micellar structures in capillary flows 5) , unstable flow in an axisymmetric abrupt contraction channel 6) , viscous fingering 7) , and the relation between pressure loss and elongation property in flows through a packed bed of particles 8) . In these studies, it was found that the flow induced structure of micelles greatly affected the flow behavior of wormlike micelle solutions.…”
Section: Introductionmentioning
confidence: 99%